Anxiety and depression: The most prevalent psychiatric disorders in the COVID-19 pandemic (Research, Society and Development, 2021)
SARS-CoV-2 infection (COVID-19) was first identified in December 2019 in Wuham, Hubei province, central China. This virus, due to its severe clinical repercussions, has forced the population to remain in social isolation, in order to avoid such repercussions. This systematic review of the literature aimed to gather and analyze the scientific content on anxiety and depression, being the most prevalent psychiatric disorders in the COVID-19 pandemic .Bibliographic references were obtained from the databases PubMed, LILACS (Latin American and Caribbean Literature in Social and Health Sciences), MEDLINE (Online System for Searching and Analyzing Medical Literature 20 articles were selected, based on the criteria of The COVID-19 pandemic has the potential to cause serious mental health problems, as with all its restrictions measures end up generating some psychosocial stressors. Among these stressors are: interruptions in routines, separation from family and friends, scarcity of daily necessities, salary discount, social isolation and school closure, which generates a significant increase in the triggering of anxiety and depression disorders in the world population.